DEVELOPMENT OF A VISUAL ACCOUNTING MODULE FOR HISTORICAL TOURISM MSMES IN TONDANO - Afnita, Vinda; Hutahaean, Lidia Aprileny; Manullang, Dominikus Rojoki; Sari, Ramda; Purba, Arjuna; Bako, Seven Marganda (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Small and Medium Enterprises (SMEs) are a crucial pillar of the Indonesian economy, yet they often face fundamental obstacles in financial management, particularly in systematic financial recording. This study aims to develop a Simple Visual Accounting Education Module to increase financial recording awareness among SMEs in the God Bless Park and Moraya Fort historical tourism area in Tondano . This research employs the Research and Development (R&D) method with the 4-D model (Define, Design, Develop, Disseminate), limited to the development stage. The module was designed based on User-Centered Design principles and the Dual Coding Theory, integrating visual elements such as illustrations, icons, and infographics to simplify abstract accounting concepts. Development involved 20 SME actors, from initial needs identification to final product testing. The results showed that the module was highly feasible and effective, with 71.4% of users rating it "Very Good" and 28.6% "Good" in the final trial. The visual approach significantly enhanced understanding, motivation, and confidence among SME actors in managing their business finances. Post-intervention, there was a notable behavioral shift from informal recording practices to systematic daily cash flow recording and simple profit-loss reporting. This study concludes that the visual accounting module is a practical, effective, and well-accepted educational medium. It serves not only as a learning tool but also as an instrument of local economic empowerment, bridging the financial literacy gap for SMEs with limited educational backgrounds. Keywords : MSMEs, financial literacy, basic accounting, visual media, educational module